Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4314/ahs.v13i2.40
|View full text |Cite
|
Sign up to set email alerts
|

The effect of unilateral vasectomy on testosterone and testicular parameters in the adult male African giant rat (<i>Cricetomys gambianus</i>)

Abstract: Background: The effects of vasectomy on spermatogenesis and reproductive parameters are recognized to be speciedependent with marked differences in levels of perturbations observed. Objectives: To assess the impact of unilateral vasectomy on testosterone level and other testicular parameters in the male African giant rat (AGR) (Cricetomys gambianus). Methods: Sixteen adult male AGRs weighing 500-1300 g were recruited for the experiment. Animals were randomly divided into three experimental groups (1-3) and one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…The changes observed in our study suggest that in KO mice, exhaustion could occur in the seminiferous tubules in a manner similar to that occurring after vasectomy (Duru et al. ). The alterations in the ductal morphologies of these mice at 6 weeks of age are basically morphometric, and the disappearance of cell proliferation and increase in cell death by apoptosis appear to be substanti‐ally relevant to this process.…”
Section: Discussionsupporting
confidence: 74%
“…The changes observed in our study suggest that in KO mice, exhaustion could occur in the seminiferous tubules in a manner similar to that occurring after vasectomy (Duru et al. ). The alterations in the ductal morphologies of these mice at 6 weeks of age are basically morphometric, and the disappearance of cell proliferation and increase in cell death by apoptosis appear to be substanti‐ally relevant to this process.…”
Section: Discussionsupporting
confidence: 74%
“…We should pay attention to the change of testoster-one level after vasectomy, because it will affect the testicular spermatogenesis function. Early animal experiments showed that testosterone levels temporarily decreased [ 78 79 80 81 ] within a short period of time (about three months) after vasectomy, possibly due to the disruption of the dynamic balance of the blood-testis barrier after vasectomy and the epididymal. The structure is impaired and its function impaired, which leads to an increase in local interleukin-1 (IL-1) levels.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the occlusion of muscle and subcutaneous layers were made using 2-0 absorbable and skin was closed with 2-0 non-absorbable sutures. Postoperatively, benzathine penicillin (Pronto Pen™) 3 [30,000 IU/kg IM once], tramadol (Tramadon™) 2 [4 mg/kg IM once] and meloxicam (Maxicam™) 4 [0.3 mg/kg SC SID for 3 days] were administered.…”
Section: Casementioning
confidence: 99%